Efecto de Antimicóticos en el tratamiento y tipificación de la dermatomicosis en cuyes - Contreras Fernández, Feliciano Andres (2025)
In this study, the effect of three antifungals was observed and the typing of dermatomycosis was carried out in guinea pigs where 60 guinea pigs with skin conditions on the face, ear and back were identified, then 20 guinea pigs each were distributed in the 3 treatments, in the first group clotrimazole was applied, in the second griseofulvin was applied and finally basic fuchsin was applied.  and it was verified every three days until his recovery, samples were also extracted to take him to the laboratory for typing, as a result he showed us that with clotrimazole he had a better recovery time of 7 days, while with the drug griseofulvin he recovered in 13 days and with basic fuchsin they recovered in 16 days. It was possible to identify 3 types of dermatomycosis which are: trichophyton mentagrophytes in 36%, trichphyton rubrum in 42% and trichophyton verrucosum in 22%. It is concluded that there is an effect on the treatments applied in the study and the differences between treatments are also seen, since clotrimazole had a shorter recovery time unlike the two treatments in the study.